Association Between Purpose in Life and Glucose Control Among Older Adults. Issue 4 (10th February 2018) - Hafez, Dina; Heisler, Michele; Choi, HwaJung; Ankuda, Claire K; Winkelman, Tyler; Kullgren, Jeffrey T
Abstract : Older adults with greater levels of purpose in life are less likely to develop type 2 diabetes or prediabetes over a 4-year follow-up compared to older adults with lower levels of purpose in life. Abstract: Background: Greater purpose in life is associated with lower rates of certain chronic diseases. Whether purpose in life can protect against development of prediabetes or type 2 diabetes is unknown. Purpose: To examine the association between purpose in life and blood glucose control among adults ≥50 years. Methods: We conducted a longitudinal cohort study of 3, 907 participants of the Health and Retirement Study who at baseline did not have type 2 diabetes or prediabetes. Baseline purpose in life was measured using the Ryff and Keyes' Scales of Psychological Well-Being and grouped into tertiles (high, medium, and low). We used multivariable linear regression to examine the association between baseline purpose in life and HbA1c over 4 years. Multivariable logistic regression was used to examine the association between baseline purpose and incident prediabetes or type 2 diabetes over the same period. Results: After adjusting for sociodemographic factors, body mass index, physical activity, and physical and mental health factors, HbA1c was 0.07 percentage points lower among participants with high purpose than those with low purpose (95% confidence interval [CI] −0.12 to −0.02; p = .011). Participants with high purpose had lower odds of developing prediabetes or type 2 diabetes than those with low purpose (adjusted odds ratio 0.78; 95% CI 0.62 to 0.98; p = .037). Conclusions: Among older adults, greater purpose in life is associated with a lower incidence of prediabetes or type 2 diabetes. Strategies to promote greater purpose in life should be tested as a part of type 2 diabetes prevention efforts.